Use pythagorean theorem
c2 = a2 + b2
c2 = 1.5^2 + 2^2
c2 = 2.25 + 4
c2 = 6.25
c = 2.5
Answer:
One solution
Step-by-step explanation:
They have isolated y for you in both equations so you can plug either one into the other.
y = 3x - 1
2x + 7 = 3x - 1
isolate the x
7 = x - 1
x = 8
Go back to the original and plug 8 into x to get y.
y = 2 (8) + 7
y = 16 + 7
y = 23
This means at (8, 23) y = 2x+7 is equal to y = 3x-1. In other words they share a point at (8, 23). This is the only solution because for any other x and y they'd not be equal.
F(x) = 2x² + 7x - 5
g(x) = -8x² - 3x + 5
g(x) + f(x) = -8x² - 3x + 5 + 2x² + 7x - 5 = - 6x² + 4x
Answer: -6x² + 4x
Answer: No, Store A is charging $2.20 per rose while Store B is charging 2.166667 dollars per rose.
Step-by-step explanation:
11/5 = 2.2
(To check) 2.2 x 5 also equals $11
However, they are not selling roses at the same rate because if you were to do 2.2x6 it will equal 13.2.
13/6 = 2.166667
Answer: Yes; 63 • 73 is equal to (6 • 7)3 or 423.
Step-by-step explanation:This is the answer because if you multiply the 6 and 7 you get 42 and you leave the exponent which in this case is 3 leaving you with 42^3